COMPENSATION OF MORAL HARM DURING IMPROPER MADICAL AID IN RUSSIA AND ABROAD - D. A. Totochenko (Russian Journal of Economics and Law)
Objective: Basing on the analysis of the Russian and foreign experience, to suggest the method of calculating the compensation of moral harm during improper medical aid. Methods: The methodological base of the research is the general dialectic method of cognition allowing to research the phenomena and processes of the reality in their historical development, interconnection and interdependence, and the general scientific, special and private legal methods. Results: The features of determining the size of compensation of moral harm during improper medical aid in Russia and abroad are researched. The method of calculating the compensation of moral harm during improper medical aid is proposed with the account of priority of under-age patients’ rights protection. Scientific novelty: The article suggests the alternative method of calculating the compensation of moral harm during improper medical aid. Another novelty is the fixed increasing coefficient which is applied if the harm is imposed on an under-age patient. Practical value: The theoretical provision formulated in the article can be applied in law-making and law-enforcement practice, as well as in the educational process of juridical educational establishments.